Crystal structure of myotoxin-II: A myotoxic phospholipase A2 - Homologue from Bothrops moojeni venom. - deAzevedo, W. F.; Ward, R. J.; Lombardi, F. R.; Giglio, JR; Soares, A. M.; Fontes, MRM; Arni, R. K. (Bentham Science Publ Bv, 1997)
The crystal structure of Myotoxin-II (MjTX-II), a Lys49 PLA(2)-homologue from Bothrops moojeni venom has been determined and refined at 2.0 Angstrom to a crystallographic residual of 19.7% (R-free = 28.1%). MjTX-II is a dimer in the crystal, with the monomers in the asymmetric unit related by a two-fold symmetry axis running through the dimer interface. The dimers of MjTX-II and the Lys49 PLA(2) from B. asper venom are similar, however the relative orientations of the monomers suggests a flexible dimer interface, which serves as a hinge between the two molecules.